Short communication. Automatic inspection of the pomegranate (Punica granatum L.) arils quality by means of computer vision - Blasco, J.=700 1 Cubero Garcia, S.; Alegre Soza, S.; Gomez Sanchis, J.
(Es, En)
Ilus., 12 ref.
Keywords: PUNICA GRANATUM; ANALISIS DE IMAGENES; CALIDAD; APLICACIONES DEL ORDENADOR; IMAGENES; FRUTAS; ESPAÑA